Growth response of some local vegetables and ornamental plants to gaseous pollutants - Muhamad, A.; Latiff, A. (Malaysian Society of Applied Biology, 1987)
Four locally grown vegetable, namely soybean, mungbean, tomato, lettuce and an ornamental plant, petunia were subjected to varying concentration of ambient air at breathing zone level and of those simulating the peak hour air pollution. At breathing zone level CO, N02 and S02 could reduce vegetative growth of all plants studied. In the fumigated air, 20-58% reduction of yield was obtained. Relative growth rate of all plants showed initial difference between the treatment but the difference become insignificant after the 4th and 5th harvest.